2013
DOI: 10.1074/jbc.m113.474346
|View full text |Cite
|
Sign up to set email alerts
|

A Gain-of-Function Mutation in the M-domain of Cardiac Myosin-binding Protein-C Increases Binding to Actin

Abstract: Background: Cardiac myosin-binding protein C (cMyBP-C) regulates heart muscle contraction by influencing actomyosin interactions. Results: Amino acids within the tri-helix bundle of the M-domain contribute to the functional effects of cMyBP-C. Conclusion: Amino acids outside of phosphorylation sites influence function of the M-domain. Significance: The tri-helix bundle is important to the regulatory role of cMyBP-C, likely through actin-binding interactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
56
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(59 citation statements)
references
References 53 publications
2
56
1
Order By: Relevance
“…5A), that is to say, we did not detect evidence of helix bundle destabilization or rearrangement (SI Appendix, Fig. S8), in contrast to a previously proposed hypothetical model (17). As our spectroscopic results suggested, we found that when this predicted protein-protein interaction site (the α-helical binding strut) is uncovered upon phosphorylation (Fig.…”
Section: Phosphorylation Unmasks the Charged Binding Strut Of The Tricontrasting
confidence: 54%
See 1 more Smart Citation
“…5A), that is to say, we did not detect evidence of helix bundle destabilization or rearrangement (SI Appendix, Fig. S8), in contrast to a previously proposed hypothetical model (17). As our spectroscopic results suggested, we found that when this predicted protein-protein interaction site (the α-helical binding strut) is uncovered upon phosphorylation (Fig.…”
Section: Phosphorylation Unmasks the Charged Binding Strut Of The Tricontrasting
confidence: 54%
“…Unlike the rest of this primarily disordered domain, a segment at the motif's C-terminal end is a well-ordered triple-helix bundle ( Fig. 1B) (15)(16)(17). We hypothesize that phosphorylation-dependent structural changes in this region are critical for the function of cMyBP-C.…”
mentioning
confidence: 99%
“…However, despite the widespread appeal of this idea, evidence that cMyBP-C limits the mobility of myosin heads via interactions with the thick filaments is still lacking. In contrast, we and others have shown that the NTDs of the cMyBP-C (e.g., C0, PA, C1, M, and C2) can bind to the TF and potently activate actomyosin interactions (14,16,29,30). The precise mechanism(s) by which cMyBP-C affects contraction is still unresolved, in part because there is a lack of understanding of how individual domains of cMyPB-C contribute to the overall effects of this multidomain protein on muscle contraction.…”
Section: Discussionmentioning
confidence: 95%
“…Force measurements with or without C0 and C1 were performed as previously described with slight modifications (29). Treatment of all animals was in accordance with the National Research Council Guide for the Care and Use of Laboratory Animals using protocols approved by the Institutional Animal Care and Use Committee at University of Arizona.…”
Section: Cryo-emmentioning
confidence: 99%
“…Assuming that C0C1f binds to the thin filament through the same contacts as C0C2, then additional sites of actin interaction must exist beyond the first 17 amino acids of the M-domain that are present in the C0C1f fragment. For example, arginines 279/280 (further along the M-domain) have been identified as critical to actin binding (9), and when mutated to alanines, they diminish the capacity of C1C2 fragments to activate thin filaments in skinned rat trabeculae (49).…”
Section: Discussionmentioning
confidence: 99%